Animal-assisted therapy with farm animals for persons with psychiatric disorders - Bente Berget; Bjarne O. Braastad (Istituto Superiore di Sanità, 2011)
Animal-assisted therapy (AAT) with farm animals for humans with psychiatric disorders may reduce depression and state anxiety, and increase self-efficacy, in many participants. Social support by the farmer appears to be important. Positive effects are best documented for persons with affective disorders or clinical depression. Effects may sometimes take a long time to be detectable, but may occur earlier if the participants are encouraged to perform more complex working skills. Progress must however be individually adapted allowing for flexibility, also between days. Therapists involved with mental health show a pronounced belief in the effects of AAT with farm animals, variation being related to type of disorder, therapist's sex and his/her experience with AAT. Research is still scarce and further research is required to optimize and individually adapt the design of farm animal-assisted interventions.